Conventional administration and scoring procedures suppress the diagnostic accuracy of a performance-based test designed to assess balance ability in lower limb prosthesis users. (August 2019) - Sawers, Andrew; Hafner, Brian J
Background: Practice effects have been observed among performance-based clinical tests administered to prosthesis-users. Their impact on test applications remains unknown. Objective: To determine whether scoring a clinical balance test using conventional procedures that do not accommodate practice effects reduces its diagnostic accuracy relative to scoring it using recommended procedures that do accommodate practice effects. Study Design: Cross-sectional study. Methods: Narrowing Beam Walking Test data from 40 prosthesis users was scored using recommended methods (i.e. average of trials 3–5) and conventional methods applied to other tests (i.e. mean or best of trials 1–3). Area under the receiver operating characteristic curve for each method was compared to 0.50, to determine if it was better than chance at identifying prosthesis-users with a history of falls, and to 0.80, to determine if it surpassed a threshold recommended for diagnostic accuracy. Results: Receiver operating characteristic curve area decreased when the Narrowing Beam Walking Test was scored using conventional rather than recommended procedures. Furthermore, when scored using conventional procedures, the NBWT no longer discriminated between prosthesis-users with and without a history of falls with a probability greater than chance, or exceeded recommended diagnostic thresholds. Conclusion: Scoring the Narrowing Beam Walking Test using conventional procedures that do not accommodate practice effects decreased its diagnostic accuracy among prosthesis-users relative to recommended procedures. Conventional scoring procedures may limit the effectiveness of performance-based tests used to screen for fall risk in prosthesis-users because they do not mitigate practice effects. The influence of practice effects on other tests, and test applications (e.g. clinical evaluation and prediction), is warranted. Clinical relevance: Scoring a clinical balance test using conventional procedures that do not mitigate practice effects reduced its diagnostic accuracy. Changing administration and scoring procedures to accommodate practice effects should be considered to improve the diagnostic accuracy of other performance-based balance tests.